Research on cross interference and evaluation method of coal mine gas detection equipment - CHEN Yongran (Gong-kuang zidonghua, 2023)
At present, coal mine underground gas detection equipment often causes false alarms or fails to alarm due to cross interference. There are potential safety hazards. There is no clear evaluation method for gas cross interference in current national or industry standards. In view of the above problems, combining with the actual underground environment gas type and volume fraction threshold in coal mines, the cross interference mechanism and characteristics of gas detection equipment based on the three commonly used principles of catalytic combustion, laser and electrochemistry are researched by using a combination method of theoretical analysis and experimental verification. The cross interference tests are designed and conducted. Combining with the common methods of gas detection equipment error testing in current standards, a gas detection equipment cross interference evaluation method based on the special gas environment in coal mines is proposed. The cross interference characteristics of the gas detection equipment are evaluated using the test method. By introducing cross interference gas samples, the cross interference value of the gas detection equipment is calculated. The value is compared with the highest precision of the equipment so as to determine if the non-target gas has a cross interference impact on the gas detection equipment. The test results show that cross interference of gas detection equipment is widespread. The methane detection equipment based on the catalytic combustion principle is easy to be interfered by sulfide and hydrogen under the specific gas environment conditions in the coal mine. Therefore, methane detection equipment should be avoided to be used in the gas environment containing hydrogen sulfide or sulfur dioxide for a long time. It will avoid poisoning or inhibiting the catalyst and affecting the measurement precision. Gas detection equipment based on the laser principle for detecting methane and acetylene is generally not affected by interference from common gases in coal mines and does not require cross interference testing. However, gas detection equipment based on the laser principle for detecting ethylene is affected by interference from methane gas. If it passes the cross interference evaluation, it can be used in a methane environment. If it fails, it should be clearly stated that the product cannot be used in environments containing methane. The cross interference characteristics of gas detection equipment based on the electrochemical principle are uncertain. It is necessary to determine the cross interference gas environment that can and cannot be used after the cross interference evaluation.